Barriers to the Implementation of Table Official at the Srikandi CUP (Indonesian Journal for Physical Education and Sport, 2021)
This research was conducted to determine the barriers to the application of the official table on Srikandi CUP Series Semarang. This research was conducted on December 14, 2020 to January 5, 2020. The subjects of this study were the official table or desk clerk and several steering committees on duty at the CUP Srikandi event. Data analysis using data reduction, display data and conclusion drawing / verification. The results obtained show that in the CUP Srikandi competition in the Semarang series, the equipment is quite complete and the tools used are all still fit for use and the tools are FIBA standard. But in the CUP Srikandi championship, there are several tools that experience obstacles that cause obstacles even though only in the initial match. The conclusion from the research results is that the equipment used at the Srikandi CUP event is quite good and still feasible and has FIBA standards.